(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
The curriculum of Portugal and Brazil determine which competences should be developed in students throughout high school. Large-scale exams in Portugal and Brazil have been applied for at least two decades. The objective of this study was to analyse the correspondence between what the official documents determine, from a perspective of competences to be developed in the students, by the biology discipline, in Portugal, and Brazil about what is requested in their National Exams. For this, an empirical study of a documentary nature was developed, which focused on the analysis of the ENEM in Brazil and the National Exams in Portugal. The body of analysis consisted of questions formulated for exams carried out between 2010 and 2016. The analysis carried out by this research evidenced the difficulty in using multiple-choice questions to test the various academic aptitudes, with a predominance of cognitive ones with 86% and 85% in phases 1 and 2, respectively of the National Exam in Portugal and 96% in the ENEM. Large-scale exams in Portugal and Brazil do not seem very suitable for promoting the training described in the official documents of both countries. Making it clear that it is not enough to develop competences in students through learning strategies and curriculum adequacy if the internal and external assessment instruments are unable to ascertain whether these competences are being developed in students.